Pengaruh Kebijakan Belt and Road Initiative Tiongkok terhadap Stabilitas Sub-Kompleks Keamanan Asia Tenggara - Mahendra, Yusril Ihza; Ramadhoan, Ruli Inayah; Suhermanto, Dedik Fitra (Jurnal Ilmiah Hubungan Internasional, 2023)
This research aims to analyze the impact of China’s Belt and Road Initiative policy on the stability of the Southeast Asia sub-regional security complex. As an analytical tool, we use the regional security complex theory which is focused on social construction variables. The results found that China used BRI as a desecuritization tool that affected the dynamics of social construction in the region. By leveraging economic and development cooperation, China seeks to eliminate threat perceptions (securitization) by forming a cooperative image towards Southeast Asian countries. The refinement in China's image can be seen from the changing pattern of alliances in the region, where countries that were previously close to the United States are now starting to show a tendency towards Beijing. In fact, Thailand and the Philippines which are Washington's closest allies in the region also show a similar trend. Moreover, we see that China's desecuritization efforts will affect ASEAN's collective ability to respond to the disputes in SCS. Previously, there were differences of opinion between member countries regarding the steps and mechanisms used to respond to China's maneuvers in SCS. Some countries show strong resistance, but some countries tend to be weak or even side with China. The existence of BRI has the potential to encourage the consolidation of attitudes among member countries. The consolidation refers to the weakening of ASEAN's attitude caused by the fading perception of securitization, and the increasingly cooperative member countries towards Beijing.   Keywords: Belt and Road Initiative; regional security complex; Southeast Asian sub-complex